An Empirical Alternative to Sidani and Thornberry’s (2009) ‘Current Arab Work Ethic’: Examining the Multidimensional Work Ethic Profile in an Arab Context - Ryan, James C. (Journal of business ethics, 2016)
While the concept of work ethic has been discussed in the Arab context (Sidani and Thornberry in J Bus Eth 91(1):35–49, 2009), the significant conceptual and methodological limitations of the existing work ethic and work value research elucidate the need for a more robust investigation of the multidimensional work ethic construct in the Arab context. Multidimensionality of the work ethic concept has gained considerable attention in recent years as researchers attempt to move away from the religiously labeled Islamic and Protestant work ethic conceptualizations. The current study examines the Arab work ethic through the use of the multidimensional work ethic profile (MWEP) on a sample of future business leaders in the United Arab Emirates. A total of 484 business students completed an Arabic version of the MWEP short form. The results show that centrality of work and hard work are the highest scoring work ethics followed by self-reliance, wasted time, and leisure. There are significant differences in work ethic dimensions across gender and categories of family breadwinner. No significant differences in work ethic dimensions are observed across categories of nationality and work preference groups. The findings are discussed in relation to the unique insight they offer on the nature of work ethic in an Arab context.